Trabeculectomy Versus Tube Outcome in Neovascular Glaucoma: Oral Presentation - Observational Study - Resident - Maharani; Syahiqoh, Daisy Syakhsiatusy; Rahmi, Fifin Luthfia; Puspasari, Denti (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesNeovascular glaucoma (NVG) is known to be a refractory form of glaucoma, which frequentlyrequires the integrated use of medical, laser and incisional surgery. Tube-shunt implantation andtrabeculectomy with antifibrotic agent are the two most-popular incisional procedures for managingrefractory glaucoma. This study aims to compare surgical outcome between patients who underwenttrabeculectomy versus tube-shunt implantation for the treatment of NVG. MethodsA retrospective study was held of NVG patients that underwent trabeculectomy and tube-shuntimplantation between January 2020 - December 2022 at Dr. Kariadi Hospital, Semarang. IOPoutcome and success rate was measured at 3 months post operatively. Statistical analysis was usedto compare the outcome between groups, p<0.05 was considered significant. ResultsThere were no significant differences in characteristics between groups at baseline. Mean IOPmeasured at 3 months post operatively was 18.58 ± 5.53 and 15.94 ± 10.79 in trabeculectomy andtube group respectively (p=0.04), complete success rate was 18.8% in trabeculectomy and 25% intube group, qualified success rate was 37.5% in trabeculectomy and 56.3% in tube group. Greaterfailure rate was observed in trabeculectomy group (43.8%). ConclusionCompared to trabeculectomy, tube-shunt implantation has lower IOP at 3 months post operatively inNVG. Greater failure rate was observed in trabeculectomy.